Evaluation of the effect of substrates and types of wheat flour on microbiological characteristics, pH values, levels of total phenolic compounds, antioxidant capacity and fermentative capacity of sourdough (Research, Society and Development, 2022)
Sourdough is a process that is expanding nowadays. However, the microorganisms present produce metabolites that can cause changes in the breads. Thus, the objective of this work was to evaluate the effects of substrates and types of wheat flour on microbiological characteristics, pH values, total phenolic compounds, antioxidant capacity and fermentative capacity of different types of sourdough, comparing them with dry yeast. In this way, six sourdough were elaborated, diversifying the type of wheat flour (whole or white) and the substrate (beer wort, pineapple juice or natural yogurt), being evaluated in the microbiological aspects (yeast count, bacteria under anaerobic conditions and under aerobic conditions), physicochemical (pH, phenolic compounds and antioxidant capacity (β-carotene/linoleic acid, ABTS and DPPH)) and fermentative capacity (only in sourdough). In view of the results obtained, it was observed that both white wheat flour and whole wheat flour, with the substrates yogurt, pineapple juice and brewer's wort, showed differences in microbiological characteristics, in pH values, in the content of compounds total phenolics, antioxidant capacity and fermentative capacity compared to dry yeast, with whole wheat flour, pineapple or beer wort providing microbial diversity, as well as lowering the pH. WY (white wheat flour and yogurt), WP (white wheat flour and pineapple) and IW (whole wheat flour and beer wort) sourdough were more resistant to temperatures (25 °C, 30 °C e 35 °C).